(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2026)
Social isolation and limited community engagement are critical challenges faced by home-bound older adults, resulting in decline in functional mobility, nutrition, and decreased access to care. This commentary highlights the potential role of trained patient navigators in the home health setting to address these social determinants of health. Patient navigators can help bridge critical service gaps and enhance overall well-being in aging populations by assessing patient’s physical, mental, and social needs and connecting them to healthcare and community resources.